The Functionality of Gray Area Ethics in Organizations - Bruhn, John G. (Journal of business ethics, 2008)
All organizations have gray areas where the border between right and wrong behavior is blurred, but where a major part of organizational decision-making takes place. While gray areas can be sources of problems for organizations, they also have benefits. The author proposes that gray areas are functional in organizations. Gray areas become problematic when the process for dealing with them is flawed, when gatekeeper managers see themselves as more ethical than their peers, and when leaders, by their own inattention, inaction, and poor modeling, minimize the importance of building a moral community by delegating gray area issues to second-tier administrators. Gray areas provide wiggle room in coping with ethical dilemmas in organizations.